2007
DOI: 10.1253/circj.71.962
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Atherogenic Alterations in T-Lymphocyte Subpopulations Related to Acute Hyperglycaemia in Type 2 Diabetic Patients

Abstract: These results suggest that acute hyperglycemia results in the progression of atherosclerosis in type 2 DM, at least in part through changes in CD4+ and CD8+28- lymphocyte subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…Our findings parallel cell culture data delineating a similar pattern of mitochondrial hyperpolarization and morphological alterations central to the inflammatory activation process of monocytes and T-cells in type 2 diabetes 7, 23 12. Specifically, the hyperglycemic state of type 2 diabetes is known to trigger the production of multiple pro-inflammatory cytokines, induce cytotoxic and helper T-cell proliferation,24 and activate immune responses in T-cells and monocytes,25 and lead to concomitant increased ROS production 26, 27,28. The heightened overall inflammatory state in type 2 diabetes likely contributes significantly to the microvascular and macrovascular complications of this disease,29 suggesting our findings may have pathophysiological relevance to the cardiovascular morbidity of diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings parallel cell culture data delineating a similar pattern of mitochondrial hyperpolarization and morphological alterations central to the inflammatory activation process of monocytes and T-cells in type 2 diabetes 7, 23 12. Specifically, the hyperglycemic state of type 2 diabetes is known to trigger the production of multiple pro-inflammatory cytokines, induce cytotoxic and helper T-cell proliferation,24 and activate immune responses in T-cells and monocytes,25 and lead to concomitant increased ROS production 26, 27,28. The heightened overall inflammatory state in type 2 diabetes likely contributes significantly to the microvascular and macrovascular complications of this disease,29 suggesting our findings may have pathophysiological relevance to the cardiovascular morbidity of diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Increased lymphocyte number is well documented as an independent risk factor for cardiovascular disease (1,2). Interestingly, decreased lymphocyte numbers also confer increased risk (3), further underlining their complex role of the immune system in atherosclerosis.…”
Section: Consequently There Has Been An Increasing Focus On the Rolementioning
confidence: 99%
“…A previous study demonstrated that facial nerve paralysis could be induced after auricular scratching followed by the depletion of CD3 + cells via an intraperitoneal injection of anti‐CD3 monoclonal antibody . In DM patients, CD3 + , CD4 + , CD8 + /CD28 − , and CD8 + /CD28 + lymphocytes are significantly decreased compared with their levels in non‐DM patients . Peripheral T lymphocytes were significantly decreased in patients with Bell's palsy in the early stage of the disease .…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we reported that facial paralysis developed more frequently in DM mice that were inoculated with HSV‐1 in the auricle . The suppression of T‐cell immunity plays an important role in the reactivation of herpes viruses, and T‐cell immunity is significantly suppressed in both DM patients and Bell's palsy patients . These two observations led to the hypothesis that HSV‐1 reactivation frequently occurs in DM patients and causes facial nerve paralysis.…”
Section: Introductionmentioning
confidence: 95%